An exotic parasitoid provides an invasional lifeline for native parasitoids. Issue 1 (20th December 2016) - Konopka, Joanna K.; Haye, Tim; Gariepy, Tara; Mason, Peter; Gillespie, David; McNeil, Jeremy N.
Abstract: The introduction of an exotic species may alter food webs within the ecosystem and significantly affect the biodiversity of indigenous species at different trophic levels. It has been postulated that recent introduction of the brown marmorated stinkbug ( Halyomorpha halys (Stål)) represents an evolutionary trap for native parasitoids, as they accept H. halys egg masses as a host but produce no viable progeny. Interspecific interactions between European egg parasitoid, Trissolcus cultratus (Mayr), and an Asian parasitoid, Trissolcus japonicus (Ashmead), were assessed by providing egg masses to T. cultratus at various time intervals following the initial parasitization by T. japonicus . The suitability of the host for the parasitoid development was re‐assessed by providing T. cultratus with fresh and frozen egg masses of various ages. The likelihood of T. cultratus being able to attack previously parasitized egg masses was determined by assessing the duration of egg mass guarding behavior by T. japonicus following parasitization. The results of experiments examining the interspecific interactions between a native European egg parasitoid, T. cultratus, and an Asian parasitoid, T. japonicus (a candidate for the biological control of H. halys ), showed that the native species can act as facultative hyperparasitoid of the exotic one. Although this is only possible during certain stages of T. japonicus development, the presence of the introduced parasitoid may reduce the impact of the evolutionary trap for indigenous parasitoid species. There is a possibility that the occurrence of facultative hyperparasitism between scelionid parasitoids associated with stinkbugs is common. This resulting intraguild predation could promote conservation and stabilization of natural communities by impacting the diversity and population dynamics of native stinkbugs and their parasitoids (e.g., by allowing native parasitoids to avoid wasting reproductive effort on unsuitable hosts), or reduce success of biological control programs (e.g., by reducing the population size of the exotic parasitoids). Abstract : The results of experiments examining the interspecific interactions between a native European egg parasitoid, Trissolcus cultratus, and an Asian parasitoid, Trissolcus japonicus (a candidate for the biological control of Halyomorpha halys ), showed that the native species can act as facultative hyperparasitoid of the exotic one. Although this is only possible during certain stages of T. japonicus development, the presence of the introduced parasitoid may reduce the impact of the evolutionary trap for indigenous parasitoid species.